2016
DOI: 10.1021/acs.iecr.6b01990
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Heavy Metals in the Presence of a Magnetic Field on Adsorbents with Different Magnetic Properties

Abstract: The application of static magnetic fields during adsorption as an unconventional method for the removal of heavy metals such as Cd2+ and Zn2+ was studied in this work. Two different materials were employed as adsorbents: activated carbon from bituminous coal and bone char. The magnetic characterization of these materials reveals that the activated carbon from bituminous coal is a ferromagnetic material, while the bone char is a paramagnetic material. Both adsorbents were used as received; i.e., no additional m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Like the source, the configuration of the magnetic field is significant in the design of an adsorption system assisted by magnetic fields, since the influence, gradient of intensity and direction will determine the type of effect in some of the adsorption phases. The configuration of the magnetic field will influence in various ways ranging from orienting, hydrating and redirecting the adsorbate, to magnetize, activate and prevent the degeneration of the adsorbent [111][112][113][114][115].…”
Section: Heavy Metalsmentioning
confidence: 99%
“…Like the source, the configuration of the magnetic field is significant in the design of an adsorption system assisted by magnetic fields, since the influence, gradient of intensity and direction will determine the type of effect in some of the adsorption phases. The configuration of the magnetic field will influence in various ways ranging from orienting, hydrating and redirecting the adsorbate, to magnetize, activate and prevent the degeneration of the adsorbent [111][112][113][114][115].…”
Section: Heavy Metalsmentioning
confidence: 99%
“…It was found that due to its ferromagnetism, activated carbon was working better under the influence of external magnetic field. There was an increase in the adsorption capacity by 63% for Cd 2+ and 15% for Zn 2+ [36]. The difference in the removal efficiency of metals in our own research and Gonzalez studies [36] is due to the time of water magnetization.…”
Section: Resultsmentioning
confidence: 47%
“…There was an increase in the adsorption capacity by 63% for Cd 2+ and 15% for Zn 2+ [36]. The difference in the removal efficiency of metals in our own research and Gonzalez studies [36] is due to the time of water magnetization. Gonzalez applied a magnetic field throughout the whole experiment duration, while the authors of this work only applied a magnetic field for a period of 10 min when water was in the raw water reservoir.…”
Section: Resultsmentioning
confidence: 47%
See 2 more Smart Citations